2018
DOI: 10.1088/1361-6382/aadc81
|View full text |Cite|
|
Sign up to set email alerts
|

The gravitational field of a laser beam beyond the short wavelength approximation

Abstract: Light carries energy, and therefore, it is the source of a gravitational field. The gravitational field of a beam of light in the short wavelength approximation has been studied by several authors. In this article, we consider light of finite wavelengths by describing a laser beam as a solution of Maxwell's equations and taking diffraction into account.Then, novel features of the gravitational field of a laser beam become apparent, such as frame-dragging due to its spin angular momentum and the deflection of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…This is in contrast to gravitational photon-photon scattering in perturbative quantum gravity discussed in [45]. In [5], we showed that the gravitational field of a laser beam considered as a proper perturbative solution of Maxwell's equations beyond the short wavelength approximation does depend on the helicity of the laser beam. In the present article, we showed that, accordingly, the polarizations of two light beams couple gravitationally; two circularly polarized light beams inflict on each other a phase shift depending on the relation between their he-licity.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 72%
See 2 more Smart Citations
“…This is in contrast to gravitational photon-photon scattering in perturbative quantum gravity discussed in [45]. In [5], we showed that the gravitational field of a laser beam considered as a proper perturbative solution of Maxwell's equations beyond the short wavelength approximation does depend on the helicity of the laser beam. In the present article, we showed that, accordingly, the polarizations of two light beams couple gravitationally; two circularly polarized light beams inflict on each other a phase shift depending on the relation between their he-licity.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 72%
“…In this section, we summarize the description of the laser beam and its gravitational field presented in [5]. A laser beam is accurately described by a Gaussian beam.…”
Section: The Gravitational Field Of a Laser Beam Beyond The Shortmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, we emphasize that the metric (2.2) is a solution of the Einstein's field equations in vacuum, so another possible aspect of the interaction between GWs and electromagnetic waves, namely, the effect of light energy-momentum tensor as a source to the curvature of spacetime will not be considered in this work, that is, light will be held as a test field only (cf. [21]).…”
Section: Modelsmentioning
confidence: 99%
“…Last, we emphasize that the metric ( 4) is a solution of the Einstein's field equations in vacuum, so another possible aspect of the interaction between GWs and electromagnetic waves, namely, the effect of light energymomentum tensor as a source to the curvature of spacetime will not be considered in this work, that is, light will be held as a test field only (cf. [27]).…”
Section: Modelsmentioning
confidence: 99%